2017
DOI: 10.1177/0192513x17720759
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Transmission of Sociability: The Mediating Role of Maternal Competence and Maternal Child-Centrism

Abstract: This study focuses on the psychological mechanisms of mothering involved in the association of maternal sociability and the sociability of their preschool children. In particular, it is posited that this association is mediated by two maternal psychological conceptualizations: (a) perception of ability to take on the role of motherhood (i.e., maternal competence) and (b) perception of distribution of resources between child and self (i.e., maternal child-centrism). Participants included 320 Jewish–Israeli moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 78 publications
1
13
0
Order By: Relevance
“…Flow-on effects of improved mental health to other family members are also a novel finding. It has been well established that poor mental health in parents, both female and male, has flow-on consequences for children ( Bowlby, 1951 ; Flouri & Buchanan, 2003 ; Lavenda & Kestler-Peleg, 2018 ; Luebbe & Bell, 2014 ; Repetti, Taylor, & Seeman, 2002 ), and that these may persist lifelong ( Fingerman, Huo, Graham, Kim, & Birditt, 2017 ; Lee et al, 2017 ; Mallers, Charles, Neupert, & Almeida, 2010 ; Stafford et al, 2015 ). Here we show that women's walking-in-nature tourism also yields benefits for partners and children.…”
Section: Discussionmentioning
confidence: 99%
“…Flow-on effects of improved mental health to other family members are also a novel finding. It has been well established that poor mental health in parents, both female and male, has flow-on consequences for children ( Bowlby, 1951 ; Flouri & Buchanan, 2003 ; Lavenda & Kestler-Peleg, 2018 ; Luebbe & Bell, 2014 ; Repetti, Taylor, & Seeman, 2002 ), and that these may persist lifelong ( Fingerman, Huo, Graham, Kim, & Birditt, 2017 ; Lee et al, 2017 ; Mallers, Charles, Neupert, & Almeida, 2010 ; Stafford et al, 2015 ). Here we show that women's walking-in-nature tourism also yields benefits for partners and children.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has suggested that parents transfer skills and behaviours to children through cognitive representations of positive, stable, and confident relationships (Bowlby, 1969;Pullataz et al, 1998). 2 Lavenda and Kestler-Peleg (2018) find that the mother's sociability (defined as perceived social support) is positively associated with their preschool child's sociability. Parents can also transfer social skills and pro-social behaviours by transferring values, perceptions of ethics and morals to children.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pratt et al (2003) show that households with authoritative parenting display greater agreement on social values between parents and children than families with less strict discipline. Lavenda and Kestler-Peleg (2018) show the mediating effect of maternal competence (defined as the extent to which a mother feels confident and capable of caring for her children) in the intergenerational transmission of sociability (perceived social support).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations